(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Land mine detection is most crucial during ware fare to deploy armed vehicle drive in the enemy territory. These armed vehicle or Main battle tanks are used to follow the path of pilot tank operated manually to avoid damage/distraction of the battle tank and defence causalities of defence crews. In addition post ware fare the mines planted during war can be detected and diffused by deploying a mine detection robot, which can save civilian life to avoid human causalities. This research work proposed to have a proto type model of a land-mine detection robot (LDR), which can be operated remotely using Wi-fi. technology. The safety of humans was addressed and designed robot with special range sensors employed to avoid obstacles. Fabrication of this project prototype was done using lightweight temperature resistant metal. A Global Positioning System (GPS) sensor is employed, which identifies and broadcasts the present location of the robot. Path planning, obstacle detection and avoidance algorithms were used to control accurately and to navigation of the proposed path by avoiding obstacles. Arduino microcontroller is employed in this robot. The robot system is embedded with metal detector capable of sensing the landmine and buzzer from producing a warning alarm to the nearby personnel in that area. The locomotion of the robot is carried out by the DC motor. The robot is interfaced with the PC by deploying a ZigBee device. In this paper, a Metal Detection System with GSM technology has been presented. The system senses or detects a metallic object and sends an alert message in form of an SMS text to an embedded security GSM number for further actions